Gender in der deutschsprachigen Kinder- und Jugendliteratur Vom Mittelalter bis zur Gegenwart - Willms, Weertje (De Gruyter, 2022)
This volume is the first to diachronously present the development of gender in German children's and young-adult literature from the middle ages to the present. It explores a topic of enormous societal relevance by examining books that have accompanied the socialization of young people on a spectrum between dominant discourses and utopian visions.